The classification and regulation of AM Radio programs - Balagosa, Sheena Marie K.; Jolo, B.Martha Alyssa B. (2013.)
The study "The Classification and Regulation of AM Radio Programs? provides us the reasons why there is a need to classify and reinforce regulation on AM radio programs based on the MTRCB guidelines, the KBP Code, and the opinion of Ilonggo radio listeners and broadcast practitioner. The study covered 12 barangays with 400 respondents and eight broadcast practitioners from four AM radio stations in Iloilo City. From the results of the study, we have found out that radio stations created program innovations that affected the listeners. There is a need to put classification in order to separate sensitive topics that are not suitable for all listeners, to protect children by knowing which programs they can listen to, to avoid hearing double meaning words, extremely violent stories and sensitive topics about sex. There is a need to reinforce regulation because of the failure to adhere to c=broadcast standards of some radio programs, KBP?s leniency in the implementation of its rules and regulation and the effectiveness of self-regulation. Thus, we have the determined that there is a need to put classification and to reinforce regulation in AM radio programs to protect the moral values of Filipino radio listeners.
Thesis (Undergraduate, Bachelor of Arts in Communication and Media Studies. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Programs -- AM Radio; Classification -- Programs -- Radio; Regulations -- Program -- Radio